Examining the transitions between living and dying roles at end-of-life. Issue 10 (26th November 2019) - Lowrie, Daniel; Ray, Robin; Plummer, David; Yau, Matthew
Abstract: Improvements in the diagnosis and disclosure of dying mean that nowadays dying people typically live with an awareness of their status for longer than they have previously. However, little is known regarding how transitions between living and dying roles occur during this time. In this grounded theory study, we investigated role transitions at end-of-life. We found that dying people periodically foreground and background living and dying selfhoods, focus on living day-by-day and goal-by-goal and reframe dying roles with an orientation to living. We argue that with better understanding of role transitions at end-of-life more compassionate and responsive care becomes possible.